Morphological Parameters of Gullies Formed on Sandy Soils and Effects of Check Dams in Central Spain - Jorge Mongil-Manso; Joaquín Navarro-Hevia; Javier Velázquez; Virginia Díaz-Gutiérrez; Ana-Carolina Toledo-Rocha (Geosciences, 2025)
Gully erosion constitutes a significant global problem, as gullies are a substantial source of sediment that harms rivers, affecting aquatic fauna and water quality, altering flow regimes, and degrading soil, among other impacts. Gullies have been extensively studied in clayey soils, where they occur more frequently, but less so in soils or materials with a sandy texture. Therefore, utilizing field measurements and aerial orthophotography, this study characterizes the morphology of a set of gullies located in the Central System mountains (central Spain), formed on sandy soils derived from granite weathering, under a Mediterranean-continental climate. Furthermore, the influence of check dams on the gully slope is also studied. The selected gullies for this study are permanent, linear, parallel, continuous, V-shaped, and semi-active. They are longer, narrower, and shallower than other gullies in significantly different soils with which they have been compared, although the width/depth ratio is similar. Additionally, check dams have considerably reduced the slope (11% on average and a 23% maximum reduction), which may result in a reduction in the flow velocity and erosive capacity. Consequently, it can be affirmed that the presence of numerous check dams significantly affects gully morphology.